2021
DOI: 10.1002/jev2.12118
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reprogramming enhances the therapeutic efficacy of osteoblast‐derived extracellular vesicles to promote human bone marrow stem cell osteogenic differentiation

Abstract: Extracellular vesicles (EVs) are emerging in tissue engineering as promising acellular tools, circumventing many of the limitations associated with cell-based therapies. Epigenetic regulation through histone deacetylase (HDAC) inhibition has been shown to increase differentiation capacity. Therefore, this study aimed to investigate the potential of augmenting osteoblast epigenetic functionality using the HDAC inhibitor Trichostatin A (TSA) to enhance the therapeutic efficacy of osteoblast-derived EVs for bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 105 publications
9
53
0
Order By: Relevance
“…Additionally, in this study, we reported that osteoblasts cultured on triangle scaffolds elicited substantially altered epigenetic functionality, resulting in increased osteogenic gene activation. Previously we demonstrated that altering the epigenome of mineralising osteoblast via HDACi induced hyperacetylation, significantly enriched secreted EVs with several pro-osteogenic microRNAs and transcriptional regulators which augmented the epigenetic landscape of recipient hBMSCs and accelerated its osteogenic capacity ( Man et al, 2021a ). Therefore, it is likely the EVs derived from osteoblasts cultured on triangle pore scaffolds were enriched with bioactive factors which modified the epigenetic landscape at recipient hBMSCs increasing its differentiation capacity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, in this study, we reported that osteoblasts cultured on triangle scaffolds elicited substantially altered epigenetic functionality, resulting in increased osteogenic gene activation. Previously we demonstrated that altering the epigenome of mineralising osteoblast via HDACi induced hyperacetylation, significantly enriched secreted EVs with several pro-osteogenic microRNAs and transcriptional regulators which augmented the epigenetic landscape of recipient hBMSCs and accelerated its osteogenic capacity ( Man et al, 2021a ). Therefore, it is likely the EVs derived from osteoblasts cultured on triangle pore scaffolds were enriched with bioactive factors which modified the epigenetic landscape at recipient hBMSCs increasing its differentiation capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Relative gene expression was evaluated as previously described ( Man et al, 2021a ). Briefly, total RNA was extracted using the RNase mini kit (Qiagen, United Kingdom) from scaffold-cultured osteoblasts according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations